Human haptic perception is interrupted by explorative stops of milliseconds - Grunwald, Martin; Muniyandi, Manivannan; Kim, Hyun; Kim, Jung; Krause, Frank; Mueller, Stephanie; Srinivasan, Mandayam A. (Frontiers in Psychology, 2014)
Introduction: The explorative scanning movements of the hands have been compared to those of the eyes. The visual process is known to be composed of alternating phases of saccadic eye movements and fixation pauses. Descriptive results suggest that during the haptic exploration of objects short movement pauses occur as well. The goal of the present study was to detect these “explorative stops” (ES) during one-handed and two-handed haptic explorations of various objects and patterns, and to measure their duration. Additionally, the associations between the following variables were analyzed: a) between mean exploration time and duration of ES, b) between certain stimulus features and ES frequency, and c) the duration of ES during the course of exploration. Methods: Five different experiments were used. The first two experiments were classical recognition tasks of unknown haptic stimuli (A) and of common objects (B). In experiment C space-position information of angle legs had to be perceived and reproduced. For experiments D and E the PHANToM haptic device was used for the exploration of virtual (D) and real (E) sunken reliefs. Results: In each experiment we observed explorative stops of different average durations. For experiment A: 329.50 ms, experiment B: 67.47 ms, experiment C: 189.92 ms, experiment D: 186.17 ms and experiment E: 140.02 ms. Significant correlations were observed between exploration time and the duration of the ES. Also, ES occurred more frequently, but not exclusively, at defined stimulus features like corners, curves and the endpoints of lines. However, explorative stops do not occur every time a stimulus feature is explored. Conclusions: We assume that ES are a general aspect of human haptic exploration processes. We have tried to interpret the occurrence and duration of ES with respect to the Hypotheses-Rebuild-Model and the Limited Capacity Control System theory.